Odpowiedzi

Najlepsza Odpowiedź!
2010-03-12T18:37:49+01:00
Zad.1
a)
6x=3
x=0,5

b)
-3x=7
x=-2⅓

c)
2x=1/5
x=0,1

d)
1,2x=4,8
x=4

e)
1/3x=3
x=9

f)
-3/5x=-5
x=8⅓

g)
3/4x=-4/9
x=-¹⁶/₂₇

h)
0,1x=-7
x=-70

Zad.2
a)
-3x=2x-10
-3x-2x=-10
-5x=-10
x=2

b)
2x-2=7-x
2x+x=7+2
3x=9
x=3

c)
10=4-2x
-2x=4-10
-2x=-6
x=3

d)
-(2x-1)=4
-2x+2=4
-2x=4-2
-2x=2
x=-1

e)
2(x+1)=x
2x+2=x
2x-x=-2
x=-2

f)
2t-(93t+1)=6
2t-93t-1=6
-91t=6+1
-91t=7
t=-¹/₁₃(jedna trzynasta)

g)
-(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10

h)
3(y+6)-y=2(y+9)
3y+18-y=2y+18
3y-y-2y=18-18
0=0

i)
(x-7)-2(93x+5)=3
x-7-186x-10=3
x-186x=3+7+10
-185x=20
x=-⁴/₃₇
2010-03-12T18:54:58+01:00
A)6x=3 /:6
x=3/6
x=1/2
b)-3x=7 /:(-3)
x=7/-3
x=-2 1/3
c)2x=1/5 /*5
10x=1 /:10
x=1/10
d)1,2x=4,8 /* 10
12x=48 /:12
x=4
e)1/3x=3 /*3
x=9
f)-3/5x=-5 /* - 5/3
x=-25/3
x=-8 1/3
///////////////////////////////////////////
a)-3x=2x-10
-3x-2x=-10
-5x=-10 /: -(5)
x=2
b)2x-2=7-x
2x+x=7+2
3x=9 /:3
x=3
c)10=4-2x
2x=4-10
2x=-6 /:2
x=-3
d)-(2x-1)=4
-2x+1=4
-2x=4-1
-2x=3/:(-2)
x=-1 1/2
e)2(x+1)=x
2x+2=x
2x-x=-2
x=-2
f)2t-(93t+1)=6
2t-93t-1=6
2t-93t=6+1
-91t=7 /: (-91)
t=1/13
g)-(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10
h)3(y+6)-y=2(y+9)
3y+18-y=2y+18
3y-y-2y=18-18
0=0
i)(x-7)-2(93x+5)=3
x-7-186x-10=3
x-186x=3+10+7
-185x=20 /:185
x=-4/37